EVALUASI PEMBANGUNAN DI BIDANG INFRASTRUKTUR DI KABUPATEN KUTAI TIMUR PASCA PEMEKARAN DAERAH - Roland Sangen Brith (Jurnal Administrative Reform, 2017)
The purpose of this study is to evaluate the development of post-expansion infrastructure of the region in East Kutai Regency which is focused on the development of road infrastructure. The period of development that is evaluated is the period of 2011-2015. The results of research Infrastructure development in East Kutai Regency for the period of 2011-2015 shows that the development of road infrastructure is still uneven due to the vast area of East Kutai Regency, constrained by funding problems, land issues with residents and weather problems. Development is hampered because the distance between each sub-district is so far that the development so far has only focused on the development of the Capital district only Sangatta.Keyword : Evaluation of Development, Infrastructure